2013
DOI: 10.1001/jamaophthalmol.2013.5305
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia, Anophthalmia, and Coloboma and Associated Ocular and Systemic Features

Abstract: IMPORTANCE Microphthalmia, anophthalmia, and coloboma form an interrelated spectrum of congenital eye abnormalities. OBJECTIVE To document the ocular and systemic findings and inheritance patterns in patients with microphthalmia, anophthalmia, and coloboma disease to gain insight into the underlying developmental etiologies. DESIGN, SETTING, AND PARTICIPANTS This retrospective consecutive case series was conducted at a tertiary referral center. Included in the study were 141 patients with microphthalmia, anoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 56 publications
0
58
2
Order By: Relevance
“…Although coloboma is a common association with microphthalmia, this does not necessarily mean that coloboma is a non-specific outcome of microphthalmia. A recent study of 141 patients with microphthalmia, anophthalmia and coloboma phenotypes revealed a similar number of microphthalmic cases without coloboma (24%) to those with optic fissure closure defects and normal globe size (23%) (65). None of the patients in the present study were clinically diagnosed as microphthalmic.…”
Section: Discussionmentioning
confidence: 95%
“…Although coloboma is a common association with microphthalmia, this does not necessarily mean that coloboma is a non-specific outcome of microphthalmia. A recent study of 141 patients with microphthalmia, anophthalmia and coloboma phenotypes revealed a similar number of microphthalmic cases without coloboma (24%) to those with optic fissure closure defects and normal globe size (23%) (65). None of the patients in the present study were clinically diagnosed as microphthalmic.…”
Section: Discussionmentioning
confidence: 95%
“…Coloboma is a congenital segmental ocular defect which can affect one or more structures of the eye; typical coloboma results in an inferior deficiency of iris, chorioretinal, and/or optic nerve tissue [13]. Ocular coloboma is believed to result from failure of normal closure of the optic fissure during embryonic eye development, termed optic fissure closure defect (OFCD) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Coloboma can occur as an isolated anomaly (simple coloboma) but in most cases it is associated with additional ocular defects, including microphthalmia, cataract, retinal detachment, and ocular motility disorders [14]. Microcornea, a reduction in the diameter of the cornea, is common in colobomatous eyes and can be associated with normal or even increased (macrophthalmic) axial length [2,3,5]. Additional systemic anomalies are present in a large proportion of patients with OFCDs including brain, skeletal, cardiac, or urogenital anomalies [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A/M can be isolated or associated with other anomalies. Anophthalmia rarely occurs in isolation, with its birth prevalence ranging from 0.6 to 4.2 per 100,000 births (Skalicky et al , 2013). …”
Section: Introductionmentioning
confidence: 99%